Performance comparison of serial and corporate feeding networks in a rectangular Microstrip patch antenna array - Soh, Ping Jack; Azremi, Abdullah Al Hadi; Dayang Khadijah, Hamzah; Rosemizi, Abd. Rahim; Mohd Taufik, Jusoh (Kolej Universiti Teknologi Tun Hussein Onn, 2009)
Organized by Kolej Universiti Teknologi Tun Hussein Onn, 19th - 20th December 2006 at Johor.